Trinomial Instrumentation: Romaniaâ€™s Quest for International Legitimacy and Representativeness - Madalina, Trandafir Miruna (Richtmann Publishing, 2012)
The present interdisciplinary research attempt proposes, by appealing to the usage of a diachronic and hermeneutical grid, tohighlight and to stance the conceptual-axiomatic instrumentation pertaining to the Romanian post-communist foreign policy, portraying,synthetically and thoroughly, the trinomial doctrine, consubstantial to the entire foreign policy strategy outlined at the governmental level.Within such a referential optics, we intend to punctually present, without claiming to be exhaustive, the trilateral format crystallized in theinternational relations spectrum, revealing the peremptory characteristics specific to the ,,openness to the world dictum â€œ, the ,,concentriccircles doctrineâ€ and the ,,axis policy via Washington-London-Bucharestâ€. Synthetically, the trinomial instrumentation advocates forRomaniaâ€™s legitimacy, representativeness, ubiquity in the external dimension, propelling it on the decisional arena of the internationalcommunity. The novelty element that the paper proposes lies in the insertion of a distinct methodology based on a psycho-cognitiveapproach, having as a unit of analysis the sum of beliefs, perceptions, axiological and normative codes in shaping preferences, optionsand foreign policy decisions. Integrally, the paper is configured as a diachronic and radiographic incursion at the level of Romaniaâ€™sexternal trajectory, revealing a distinguished conduct imprinted by the complexity and substance of a trinomial instrumentation.